Addressing the mental health needs and burdens of children fleeing war: a field update from ongoing mental health and psychosocial support efforts at the Ukrainian border. Issue 2 (19th December 2022) - Schwartz, Lyla; Nakonechna, Mariia; Campbell, Georgina; Brunner, Donja; Stadler, Christina; Schmid, Marc; Fegert, Jörg M.; Bürgin, David
ABSTRACT: Background: The ongoing horrors of the war in Ukraine have led to enormous consequences: loss of life, severe injuries, and mass movements of civilians. Exposure to war, living in conflict zones, and forced displacement increase the risk of experiencing a broad spectrum of direct and indirect burdens towards physical and mental health, in particular among children. Objective: This letter to the editor aims to provide multiple clinical and 'mental health and psychosocial support' (MHPSS) systems' perspectives by experts working in ongoing aid efforts to bridge and disseminate their current observations towards child and adolescent mental health services involved in the mental health response to the current war in Ukraine. Results and Discussion: The diverse perspectives from three mental health professionals involved in the MHPSS response highlight the different burdens and needs of children being confronted with situations of an existential nature. Children live through transformed social situations, deteriorated life conditions, general uncertainty, and encounter numerous losses. As such, war is the ultimate non-normative and existential stressor. The four perspectives highlight the need to: (1) adjust help toward the needs of the beneficiary, (2) understand help efforts as intersubjective human encounters and enable parents and caregivers in these encounters, (3) recognise losses and embrace finding ways to facilitate grief, and (4) continue to address these needs in a coordinated way that follows inter-agency guidelines. Conclusion: Better understanding the needs of refugee children underlines the importance of investing in their future by providing resources for humanitarian aid and psychosocial interventions during sustained emergencies. The perspectives presented in this letter emphasise that psychosocial care is deeply rooted in intersubjective help-encounters and, therefore, a professionalisation of interventions should co-occur with their humanisation and be adapted to subjective needs, varying sociocultural backgrounds, and the individuals themselves with the goal of reducing suffering and fostering well-being. HIGHLIGHTS: The three expert humanitarian aid perspectives highlight the need to: adjust help toward the needs of the beneficiary, understand help efforts as intersubjective human encounters and enable parents and caregivers in these encounters, recognise losses and embrace finding ways to facilitate grief, and continue to address these needs in a coordinated way that follows inter-agency guidelines.